Hubungan Perilaku Hidup Bersih dan Sehat (PHBS) dengan Status Gizi Balita di Desa Sidorejo Lendah Kulon Progo Yogyakarta - Nuzuliana, Rosmita; Alviolita, Shineka Nur (Poltekkes Kemenkes Padang, 2023)
PHBS is one of the indirect factors on the nutritional status of toddlers. Health behavior problems in early childhood are related to personal hygiene and the environment. A preliminary study conducted on 10 respondents in Sidorejo Village showed that out of 10 indicators of PHBS, mothers who carried out 1-3 indicators had 1 toddler with poor nutritional status, mothers who carried out 4-5 indicators had 4 toddlers with malnutrition status, and mothers who do 8-10 indicators have five children with good nutritional status. This study aims to determine the relationship between clean and healthy living behavior and the nutritional status of toddlers in Sidorejo Lendah Kulon Progo Village, Yogyakarta. The research method uses cross-sectional analytic with the Cluster Random Sampling technique with a population of 456, a sample of 100 respondents and PHBS data collection in the form of a questionnaire. The results of this study are that there is a relationship between PHBS and the nutritional status of toddlers in Sidorejo Lendah Kulon Progo Village, Yogyakarta. In conclusion, there is a significant relationship (0.001) with a close relationship in the low category with a correlation value (0.295). The suggestions are expected to improve good PHBS, the better the implementation of PHBS for mothers, the smaller the risk of toddlers experiencing malnutrition status.